Oral delivery of Hyperimmune bovine serum antibodies against CS6-expressing enterotoxigenic Escherichia coli as a prophylactic against diarrhea. Issue 1 (9th November 2020) - Talaat, KR; Porter, CK; Bourgeois, AL; Lee, TK; Duplessis, CA; Maciel, M; Gutierrez, RL; DeNearing, B; Adjoodani, B; Adkinson, R; Testa, KJ; Feijoo, B; et al.
ABSTRACT: Background: . Oral administration of bovine antibodies active against enterotoxigenic Escherichia coli (ETEC) have demonstrated safety and efficacy against diarrhea in human challenge trials. The efficacy of bovine serum immunoglobulins (BSIgG) against recombinant colonization factor CS6 or whole cell ETEC strain B7A was assessed against challenge with the CS6-expressing B7A. Methods: . This was a randomized, double-blind, placebo-controlled trial in which healthy adults received oral hyperimmune BSIgG anti-CS6, anti-B7A whole cell killed or non-hyperimmune BSIgG (placebo) in a 1:1:1 ratio then challenged with ETEC B7A. Two days pre-challenge, volunteers began a thrice daily, seven day course of immunoprophylaxis. On day 3, subjects received 1 × 10 10 CFUs of B7A. Subjects were observed for safety and the primary endpoint of moderate-severe diarrhea (MSD). Results: . A total of 59 volunteers received product and underwent ETEC challenge. The BSIgG products were well-tolerated across all subjects. Upon challenge, 14/20 (70%) placebo recipients developed MSD, compared to 12/19 (63%; p = .74) receiving anti-CS6 BSIgG and 7/20 (35%; p = .06) receiving anti-B7A BSIgG. Immune responses to the ETEC infection were modest across all groups. Conclusions: . Bovine-derived serum antibodies appear safe and well tolerated. Antibodies derived from cattle immunized with whole cell B7A provided 50% protection against MSD following B7A challenge; however, no protection was observed in subjects receiving serum antibodies targeting CS6. The lack of observed efficacy in this group may be due to low CS6 surface expression on B7A, the high dose challenge inoculum and/or the use of serum derived antibodies versus colostrum-derived antibodies.